Students’ Response towards Game Use as a Warming-up Activity in TEYL - Isna Humaera; Rahmadina Mukhtar (IAIN KENDARI, 2021)
This research aims at investigating on how students’ response toward the use of games as warming up activity in teaching English for young learners. This research is implemented by the researchers to teach English in classroom by using games in the beginning of lesson for eight meetings. The data were collected by using observation, questionnaire, and students’ reflection. The collected data were analyzed by using qualitative methods. The result of the study shows that when games use as warming up activity, it is entertaining in that it makes students feel fun and happy while learning. This study suggests that English teacher can use games as teaching method since games give pleasant class atmosphere and make students relax.Keywords: Games; Warming up activity; Young learners.